DNA adducts of antitumor cisplatin preclude telomeric sequences from forming G quadruplexes - Heringova, Pavla; Kasparkova, Jana; Brabec, Viktor (Journal of biological inorganic chemistry, 2009)
We studied the effect of antitumor cisplatin and inefficient transplatin on the structure and stability of G quadruplexes formed by the model human telomere sequence 5'-GGG(TTAGGG)(3)-3' using circular dichroism, UV-monitored thermal denaturation, and gel electrophoresis. In addition, to investigate whether there is a connection between the ability of cisplatin or transplatin to affect telomerase activity and stability of G quadruplexes, we also used a modified telomere repeat amplification protocol assay that uses an oligonucleotide substrate for telomerase elongation susceptible to forming a G quadruplex. The results indicate that cisplatin is more efficient than transplatin in disturbing the quadruplex structure, thereby precluding telomeric sequences from forming quadruplexes. On the other hand, the results of this work also demonstrate that in absence of free platinum complex, DNA adducts of antitumor cisplatin inhibit telomerase catalysis, so the mechanism underlying this inhibition does not involve formation of the G quadruplexes which are not elongated by telomerase.
Keywords: denaturace nukleových kyselin; tranzitní teplota; sekvence nukleotidů; adukty DNA; Biocatalysis; Transition Temperature; telomerasa; protinádorové látky; Telomere; techniky amplifikace nukleových kyselin; spektrofotometrie ultrafialová; elektroforéza v polyakrylamidovém gelu; G-Quadruplexes; Circular Dichroism; Nucleic Acid Denaturation; Nucleic Acid Amplification Techniques; Spectrophotometry, Ultraviolet; Electrophoresis, Polyacrylamide Gel; lidé; Telomerase; Humans; telomery; DNA Adducts; cirkulární dichroismus; biokatalýza; cisplatina; Base Sequence; G-kvadruplexy; Cisplatin; Antineoplastic Agents